Menghadapi Ancaman Nasionalisme Disintegrasi Bangsa di Tengah Trend Kabur Aja Dulu - Putri Sari Margaret Julianty Silaban; Diya Mirza; Nida Nafilah; Surya Zulfachrinal Tanjung (Jurnal Bintang Pendidikan Indonesia, 2025)
The hashtag #KaburAjaDulu has become a trending topic on social media as a form of protest and criticism from the public regarding Indonesia's economic, political, and social conditions. Many people feel that the government is not pro-people in making policies and accommodating public aspirations. This phenomenon has emerged in response to various domestic issues, such as high education costs, limited job opportunities, and wages that are considered inadequate. The hashtag has become a symbol of disappointment toward economic conditions, social issues, and government policies that are seen as unfavorable to the public. Many netizens use #KaburAjaDulu on social media to share information about job vacancies, scholarships, and experiences of living abroad, as an invitation to seek a better life outside of Indonesia.